A Interlocução entre a diplomática contemporânea e a documentoscopia no reconhecimento de falsificação documental - GOMES NETO, Milton Bezerra (2022)
Year by year, the humans were increasing their cognitive abilities of to handle, create and save their documents. However, their natural wishes to be the best in the society still remains revealed, many times, even to illegal practices. A way that practice was used it’s by document forgery, this researching has as a goal is analyzing the elements of ID card issued by Civil Police of State of Para (PCPA) starting by concepts and techniques related to contemporary diplomacy and documentology, as the intent to appreciate your techniques to recognize the authenticity of the particular document, in this case, ID card, observing correlated points so that an interlocution could be proposed aiming at a better analysis of the document, as well as to show the contribution of the Archivist in the staff of the Civil Police, such goals will be achieved after we develop the concepts of the two sciences through a survey bibliographic and the valuation and proposition of authenticity verification standards, the present survey was created by articles, books, sites and periodicals, civil documents and Documentology; based on the studies the correlation of the sciences in assigning probative value and the authenticity to the documents the was also a need for further studies on the subject, given that the theme could be inserted into the pedagogical project of the Archival course as an optional subject opening another range of possibilities for Archivist Science as well as Archivist